Using The Development Life Cycle (SDLC) System As A Retail Sales Information System - Prihatiningsih, Tri; Suhandini, Yustina; Santikai, Dewi (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
This study aims to solve problems experienced at the Six Store Probolinggo Store where data recording and investigation of sales and purchase transactions still use manual goods receipts. When checking the size or stock of goods for each product when purchasing at offline user sales, the user still has to wait to find out whether stock is still there or not and the high error rate that occurs.The Six Store store needs a  way to solve  the  problems  that  occur,  so  the  researchers  created  a  system  design  using  the  System  Development Life  Cycle  (SDLC)  method.  This  method  was  chosen  because  SDLC  can  measure  and  improve  the  sales process  more  effectively,  minimize  operational  costs  and  increase  revenue  throughout  the  day.  While programmers  use  VB  6.0-based  applications  and  Ms.  Access.  It  can  be  concluded  if  there  is  progress produced by the news system. This proves that regular financial bookkeeping can affect the results of the sale itself.This News System is able to obtain sales reports per note, per item variant, per item and inventory reports in such a short time according to user needs. The results of the application of the Information System show an increase in turnover of 75% every year at the Six Store Probolinggo Store.